Aligning Financial Supervisory Structures with Country Needs - Carmichael, Jeffrey (Washington, DC: World Bank, 2013)
this book is the result of a World Bank conference on regulatory structure organized to give policymakers an opportunity to reflect on the worldwide trend toward structural change and, in particular, the amalgamation of regulatory agencies. Within this trend, a number of competing models of regulatory structure have emerged, each with its group of proponents. These models range from an institutional structure in which each regulatory agency is assigned to a group of industry participants, through varying degrees of regulatory integration, to a unified structure in which all key regulatory responsibilities are combined within one agency. Rather than highlight one-or more-model as necessarily superior to the others, the conference sought to take an objective and balanced approach to the topic. This objective is reflected in a number of the presentations gathered here, including chapter 2, which, by providing a balanced overview of the alternatives, outlines the spectrum of possibilities and the range of issues that might influence the decision to choose a particular structure in a given situation. The conference was structured around three themes: the choice of an appropriate structure for regulation, problems relating to management of the transition to a new structure, and issues involved in implementing the new regime effectively.